Chitosan/hydroxyapatite nanocomposite scaffolds to modulate osteogenic and inflammatory response. Issue 2 (31st July 2021) - Soriente, Alessandra; Fasolino, Ines; Gomez‐Sánchez, Alejandro; Prokhorov, Evgen; Buonocore, Giovanna Giuliana; Luna‐Barcenas, Gabriel; Ambrosio, Luigi; Raucci, Maria Grazia
ABSTRACT: Considerable attention has been given to the use of chitosan (CS)‐based materials reinforced with inorganic bioactive signals such as hydroxyapatite (HA) to treat bone defects and tissue loss. It is well known that CS/HA based materials possess minimal foreign body reactions, good biocompatibility, controlled biodegradability and antibacterial property. Herein, the bioactivity of these composite systems was analyzed on in vitro bone cell models for their applications in the field of bone tissue engineering (BTE). The combination of sol–gel approach and freeze‐drying technology was used to obtain CS/HA scaffolds with three‐dimensional (3D) porous structure suitable for cell in‐growth. Specifically, our aim was to investigate the influence of bioactive composite scaffolds on cellular behavior in terms of osteoinductivity and anti‐inflammatory effects for treating bone defects. The results obtained have demonstrated that by increasing inorganic component concentration, CS/HA (60 and 70% v/v) scaffolds induced a good biological response in terms of osteogenic differentiation of human mesenchymal stem cells (hMSC) towards osteoblast phenotype. Furthermore, the scaffolds with higher concentration of inorganic fillers are able to modulate the production of pro‐inflammatory (TGF‐β) and anti‐inflammatory (IL‐4, IL‐10) cytokines. Our results highlight the possibility of achieving smart CS/HA based composites able to promote a great osteogenic differentiation of hMSC by increasing the amount of HA nanoparticles used as bioactive inorganic signal. Contemporarily, these materials allow avoiding the induction of a pro‐inflammatory response in bone implant site.